AMOEBIC LIVER ABSCESS: A COMPARATIVE STUDY OF NEEDLE ASPIRATION VERSUS CONSERVATIVE TREATMENT - Zafar, Arshad; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 2002)
BACKGROUND: Amoebic liver abscess is a serious problem in Pakistan. Its management includes antimicrobial drugs, needle aspiration and surgical drainage. This study was done to see the therapeutic efficacy, safety and outcome of ultrasound guided needle aspiration of amoebic liver abscess combined with antiamoebic drugs. METHODS: This was a prospective study with a minimum follow up of six months comparing the results of needle aspiration plus antiamoebic drugs with drug treatment alone in Amoebic Liver Abscess. It was carried in Surgical '˜B' Unit of Ayub Teaching Hospital from July 1998 to June 2001. The patients were divided into two groups. Group A with abscess <300 cm3 were treated with drugs alone. Group B patients with abscess >300 cm3 or smaller abscesses which failed to respond to medical treatment were treated with both needle aspiration and drugs. Main outcome measures were abdominal pain, fever, anorexia, hepatomegaly, resolution of amoebic liver abscess on ultrasound, length of hospital stay and any complications. RESULTS: There were 46 patients in the study group. 21 (45.5%) patients were in Group A and 25 (54.5%) in Group B. The ages ranged from 15-70 years. 38 patients were male and 8 were females. The right lobe was involved in 44 (95.5%) patients and left lobe in 2 (4.5%) patients. Mean volume of abscess in Group A was 225 cm3 and in Group B was 560 cm3. Needle aspiration was successful in 24 (96.3%) patients and failed in 1 (3.7%) patient. The mean time of clinical improvement was 7 and 3 days respectively in Groups A and B. The mean hospital stay was shorter in Group B (3.5 day) than Group A (7.5 days). The resolution of abscess seen on ultrasound was rapid in Group B. Complications occurred in only one patient in Group B. No mortality was seen in any group. CONCLUSIONS: Needle aspiration combined with antiamoebic drugs is more effective than drug treatment alone in the management of amoebic liver abscess.